2016
DOI: 10.1038/ncomms11537
|View full text |Cite
|
Sign up to set email alerts
|

The TatD-like DNase of Plasmodium is a virulence factor and a potential malaria vaccine candidate

Abstract: Neutrophil extracellular traps (NETs), composed primarily of DNA and proteases, are released from activated neutrophils and contribute to the innate immune response by capturing pathogens. Plasmodium falciparum, the causative agent of severe malaria, thrives in its host by counteracting immune elimination. Here, we report the discovery of a novel virulence factor of P. falciparum, a TatD-like DNase (PfTatD) that is expressed primarily in the asexual blood stage and is likely utilized by the parasite to counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 42 publications
(45 reference statements)
0
57
0
Order By: Relevance
“…The twin-arginine translocation (tat) system has been shown to play an important role in the virulence of Yersinia pseudotuberculosis ( Lavander et al, 2006 ) and has been associated with E. coli meningitis ( Siddiqui et al, 2012 ). Although the function of the tatD component is not fully known, it has been reported to be the virulence factor in Plasmodium and a potential vaccine candidate for malaria ( Chang et al, 2016 ). We had previously reported thymidylate kinase and 30S ribosomal protein S3 as being suitable for the distinction of M. massiliense from other mycobacteria including other subspecies of the M. abscessus complex ( Tan et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…The twin-arginine translocation (tat) system has been shown to play an important role in the virulence of Yersinia pseudotuberculosis ( Lavander et al, 2006 ) and has been associated with E. coli meningitis ( Siddiqui et al, 2012 ). Although the function of the tatD component is not fully known, it has been reported to be the virulence factor in Plasmodium and a potential vaccine candidate for malaria ( Chang et al, 2016 ). We had previously reported thymidylate kinase and 30S ribosomal protein S3 as being suitable for the distinction of M. massiliense from other mycobacteria including other subspecies of the M. abscessus complex ( Tan et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…During infection, multiple parasite toxins are released at the time of iRBC rupture. These toxins include the malaria pigment, a by-product of heme degradation by the parasite (7678), glycophosphatidylinositol (GPI) moieties that are present in many merozoite proteins, a TatD-like DNase (79), a tyrosine-tRNA synthase (80), or lipids extracted from P. vivax schizonts (81). Protection from disease by anti-toxins antibodies has been demonstrated experimentally using synthetic glycans mimicking GPI (82).…”
Section: Mechanisms Of Immunity Against the Malaria Parasitementioning
confidence: 99%
“…TatD is a protein that is widely presented and conserved in various species, both prokaryotes and eukaryotes (Wang et al, 2018), and it is also involved in the DNA-repair system, in apoptotic cell death and in cleaving neutrophil extracellular traps (Chang et al, 2016;Chen, Shen et al, 2014;Gannavaram & Debrabant, 2012;Qiu et al, 2005). A variety of genes encoding TatD-like proteins, including a single conserved TatD domain consisting of approximately 250 amino acids, have been reported (Chen, Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of genes encoding TatD-like proteins, including a single conserved TatD domain consisting of approximately 250 amino acids, have been reported (Chen, Li et al, 2014). However, while these proteins have been widely investigated in Gramnegative bacteria (Chen, Li et al, 2014;Matos et al, 2009;Chang et al, 2016), represented by Escherichia coli, little has been reported regarding the structural and functional properties of TatD-like proteins in Gram-positive bacteria. SAV0491, a putative deoxyribonuclease from the Grampositive bacterium Staphylococcus aureus (Mu50 strain), shares sequence identities of 30% and 34% with the TatD proteins from E. coli and Homo sapiens, respectively.…”
Section: Introductionmentioning
confidence: 99%